Sistem Pendukung Keputusan Penerimaan Bantuan Dana Desa BLT dengan Metode SAW Berbasis WEB - Faisal, Ahmad; Rusda, Depi (STMIK Budi Darma, 2022)
The object of research that will be made is to determine the receipt of village funds in the village of Kampung Melayu, namely Direct Cash Assistance (BLT) according to system rules. The purpose of previous research regarding research on determining recipients of rice social assistance to the poor in Kampung Melayu village with the Simple Additive Weighting (SAW) method aims to determine prospective recipients of poor rice to complete practical decision making and have alternative choices for decision making in order to determine poor people who are entitled to receive rice social assistance for the poor (Raskin) in the village. Based on the criteria used to determine the decision to receive rice social assistance for the poor, namely the amount of income, marital status, number of dependents and age. The results of this study are shown for the village government to be able to determine the people who are entitled to receive social assistance for poor rice (Raskin)